Improving learners’ representational coherence ability with experiment-related representational activity tasks - Jochen Scheid (American Physical Society, 2019)
Proper understanding of and learning from physics phenomena and experiments requires—among other competencies—flexible and coherent use of multiple representations (MRs). These can include everything from the “enactive” or “operational” manipulation of the experimental devices and materials to the most abstract level of a mathematical formulation of the phenomenon investigated in a given experiment. An essential prerequisite for effective work with MRs is the ability to achieve coherence between different representations. However, research indicates that the level of representational coherence ability of learners across various age groups is low. In order to improve this state of affairs, an intervention study about the use of MRs related to physics experiments was carried out (content area geometrical optics). Specific learning tasks (representational activity tasks, RATs) were designed which explicitly require various types of coherent connections, such as comparing, completing, and correcting representations. In a quasiexperimental repeated measurement study (N=302) using a multilevel analysis for measuring changes, a comparison of a treatment group learning with RATs vs a control group learning with conventional tasks was carried out (with identical content, lesson plans, and duration of the intervention in both groups; moreover, each of the four schools had corresponding classes of both groups. They were taught by the same teacher). Results showed a highly significant and practically relevant effect on students’ representational coherence ability (p<0.001; d=0.69). The positive effect of RATs could still be found six weeks after the end of the intervention (p<0.001; d=0.43). Several covariates (gender, pre-instructional knowledge in physics, mathematics, three facets of intelligence) were analyzed, with no or small influence on these effects. Finally, some limitations and implications of the study for classroom practice and further research are discussed.